Multi‐Electrode Printed Bioelectronic Patches for Long‐Term Electrophysiological Monitoring - Reis Carneiro, Manuel (2022)
A novel architecture of materials and fabrication techniques is proposed that serves as a universal method for implementation of thin-film biostickers for high resolution electrophysiological monitoring. Unlike the existing wearable patches, the presented solution can be worn for several days, and is not affected by daily routines such as physical exercise or taking bath. A printable biphasic liquid metal silver composite is used, both as the electrical interconnects and the electrodes. This allows combining advantages of dry electrodes, i.e., printability and non-smearing behavior, with benefits of wet electrodes, i.e., high-quality signal. A human subject study showed that these biphasic printed electrodes benefit from a lower electrode-skin impedance compared to clinical grade Ag/AgCl electrodes. Digital printing enables autonomous fabrication of biostickers that are taylor-made for each user and each application. A universal miniaturized electronic system for biopotential acquisition and wireless communication is develpoed, and demonstrated multiple biopotential acquisition cases, including electrocardiography, electroencephalography, electromyography, and electrooculography.